FINITE DIRECT SUM ON SEMI-COHEREDITARY MODULE PROPERTIES - Lestari, Rizza
This thesis deals with finite direct sum of hereditary and cohereditary modules and the finite direct sum of semi-hereditary modules. These results were developed to investigate the finite direct sum of semi-cohereditary modules with specific condition. In this thesis, we investigate some properties of injective modules so they can be adapted to weakly injective modules as well. The main results is the structure of finite direct sum of semi-cohereditary modules, that is, semi-cohereditary modules with specific condition through the weakly injective module properties. Furthermore, we also provide a survey of hereditary and cohereditary module properties and a survey of semi-hereditary and semi-cohereditary module properties.